2020
DOI: 10.3389/fenvs.2020.570637
|View full text |Cite
|
Sign up to set email alerts
|

Field Testing a Pilot-Scale System for Alkaline Dehydration of Source-Separated Human Urine: A Case Study in Finland

Abstract: Alkaline dehydration can treat human urine to produce a dry and nutrient-rich fertilizer. To evaluate the technology at pilot-scale, we built a prototype with capacity to treat 30 L urine d −1 and field tested it for the first time at a military training camp in Finland. We operated the system for 3 months and monitored the recovery of nutrients, end-product composition, physicochemical properties and energy consumption. Results revealed that the system received less urine than anticipated, but achieved high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…All the substrates apart from pure MgO had similar EC, approximately 25 mS•cm −1 when measured as 1:5 (substrate: urine) suspensions. Compared to the initial EC, the endproducts had higher EC because of accumulation of urine salts [Simha et al (2020a) for more information on the salt content of dried urine fertilizer]. The EC of the urine added to the treatment was 11.7 ± 1.2 mS•cm −1 .…”
Section: Physicochemical Propertiesmentioning
confidence: 98%
See 2 more Smart Citations
“…All the substrates apart from pure MgO had similar EC, approximately 25 mS•cm −1 when measured as 1:5 (substrate: urine) suspensions. Compared to the initial EC, the endproducts had higher EC because of accumulation of urine salts [Simha et al (2020a) for more information on the salt content of dried urine fertilizer]. The EC of the urine added to the treatment was 11.7 ± 1.2 mS•cm −1 .…”
Section: Physicochemical Propertiesmentioning
confidence: 98%
“…Several promising technologies at various scales are being developed across the world for the on-site treatment of urine (Harder et al, 2019). One among these technologies is alkaline dehydration (Simha et al, 2020a;Simha et al, 2020b;Simha et al, 2020c), where urine is dried to produce a solid fertilizer with 10-30 times higher concentrations of plant nutrients than what is originally present in freshly excreted urine. The treatment involves alkalizing urine (pH ≥ 10) to inhibit the enzyme-catalyzed hydrolytic degradation of urea (Krajewska, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introducing a treatment with activated carbon between biological treatment and distillation resulted in a safe fertilizer product with a sufficiently low content of organic micropollutants to obtain an unlimited fertilizer allowance from the Swiss authorities, without co-removal of beneficial nutrients. 63 At the bathroom scale, Simha et al 64 tested alkaline dehydration at pilot-scale for the production of a volume-reduced dry, transportable fertilizer. With this technology, fresh urine is dehydrated by a forced air stream within an alkaline medium.…”
Section: The Socio-technical Challenges Of Urine Source Separationmentioning
confidence: 99%
“…They conclude that it is very much possible to ideally supply at least 20% of the total nitrogen demand for food production globally with urea recovery from urine. In a pilot study done in Finland, Simha et al (2020) [66] have shown that source-separated urine can be subjected to alkaline dehydration and converted to a dry, nitrogen-rich fertiliser. Such separation to recover nitrogen from human wastes upstream, instead of recovering just a part of it as ammonium sulphate at wastewater treatment plants [36], can lead to greater biomethane production when the relatively nitrogen-poor stream of human excreta is anaerobically digested.…”
Section: Municipal and Industrial Solid Waste And Sewage Managementmentioning
confidence: 99%